POSISI TANAM RUMPUT LAUT DENGAN MODIFIKASI SISTEM JARING TERHADAP PERTUMBUHAN DAN PRODUKSI Eucheuma Cottonii DI PERAIRAN PANTURA BREBES - A. Ilalqisny Insan; Dwi Sunu Widyartini; Sarwanto Sarwanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
Eucheuma cottoni is a kind of seaweed which is potential as an export comodity and commonly culturated in the coastal area Brebes regency has a coastal line of approximately 53 km including 14 village and 5 subdistrict from Randusanga wetan to Limbangan Losari This coastline has not been used optimally. The demands for the seaweed is increasing, so that the seaweed culture should be developed continually. This study was aumed to find out the growth and production of Eucheuma cottoni which is the highest and planning position by modifying net system. This study has been done from June-October 2012. The experimental design was randomized block design. The treatment include (I) Planting position, vertical : (P1), horizontal (P2), system modification: (M1) single string, (M2)waring net (M3) tube net, (M4) tubular net. The growth of cottoni is increasing following the age either for the vertical on horizontal by net system modification. The highest result(10,83 g/days) were reached for the treatment of open waring net (7150 g/m2), with the water condition of in Pandansari with salinity 32-35 ‰ for Temperatur 27-30 C and pH 7-8.